The Effects of Video-Based Teaching Materials on Students’ Listening Ability - Masbirorotni; Hustarna (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
Finding appropriate teaching materials for listening subjects is not an easy task for lecturers. Therefore, creating video-based teaching materials is one of the solutions. However, the effectiveness of this product is still unknown. This quasi-experimental research aims to determine the effects of using video-based teaching materials on the listening ability of first-semester English students. Samples were taken using the cluster sampling technique, two classes out of 3 existing classes. The control class was treated using only audio media, while the experimental class was treated with audio-visual (video) media. The treatment was conducted for 14 meetings for each class, starting with giving the pre-test and ending with giving the post-test. The results of independent sample t-test calculations revealed that there was no significant difference in the learning outcomes between the control and experimental classes. This is evidenced by the sig. (2-tailed) value, namely 0.855>0.05. However, the range of the pre-test and post-test results between the control and experimental classes is different. The score range for the control class was 17.22, while the score range for the experimental class was 33.05. This shows that the use of video in the experimental class had a higher effect on improving students' listening skills than in the control class, which was only taught with audio materials.